The Role of Stakeholders in Natural Tourism Management of Kapopo Forest Park, Central Sulawesi - Arman Maiwa; Abdul Rahman; Hendra Pribadi; Hamka Hamka; Rhamdani Fitrah Baharuddin; Gerry Jardan (Universitas Andi Djemma Palopo, 2023)
The main challenge in managing Kapopo natural tourism is the participation of stakeholders who have an interest in its management. The importance of understanding and involvement of stakeholders in the management of Kapopo natural tourism can be seen from the achievement of sustainability in Kapopo natural tourism, which cannot be achieved optimally without effective cooperation between all parties involved. So instruments are needed to involve every stakeholder as the key to the success of Kapopo natural tourism. This research examines the role of stakeholders who have an interest and influence in supporting the successful management of Kapopo Nature Tourism in Central Sulawesi. The method uses qualitative descriptive analysis to see the role of stakeholders, as well as influence and interest analysis to see the influence and interests of each stakeholder in managing Kapopo natural tourism. The results of this research identified 13 stakeholders who have various roles, of which the Forestry Service and the Grand Forest Park Manager are key stakeholders in the management of Kapopo natural tourism. In this research, it was also found that in general the relationship between stakeholders was good, but there were several stakeholders who had different views which had the potential for conflict and could influence the management of Kapopo natural tourism.